Verification pathologies: an analysis of ceasefire verification missions in Angola, Mozambique and Kosovo - Burridge, R (2019)
The UN and other international organisations (IO) routinely deploy ceasefire verification missions (CVM) in support of international peacekeeping. The positive contributions CVMs can make are reliant on understandings by the conflict parties and by the international community that CVM reporting is impartial, the product solely of data gathered and analysed in a manner that is rational and objective. This thesis examines this assumption by asking, 'To what extent can factors other than monitoring data affect the content of ceasefire verification reports?' The research constitutes a series of plausibility probes on groups of factors that could theoretically affect a CVM's output so as to result in some non-trivial change to the international effect that output would likely have. Factor indicators and counter-indicators were derived and applied to three typical cases from a universe of 68 post-War CVMs: the UN Angola Verification Mission II (1992), the UN Operation in Mozambique (1992-4), and the OSCE Kosovo Verification Mission (1998-9). Sources (many previously unpublished) were drawn from archives in New York, Prague and Oxford, and from private collections, and supplemented with interviews with former CVM participants and expert commentators. The thesis demonstrates that the following 'verification pathologies' can substantially affect ceasefire verification reports: productive language and proscriptions in the CVM mandate and the ceasefire agreement(s); organisational dysfunction in the CVM, the conducting IO and the nexus between them; certain processes upon which CVMs are based; certain CVM procedures; moderation or suppression of information by the conducting IO in pursuit of its strategic purposes; manipulation by powerful actors. The thesis offers ways in which those who conceive, design and conduct CVMs could seek to moderate the influence of these pathologies, and urges a more critical reading of CVM outcomes and consequent historical events.